SYSTEMATIC REVIEW EFEKTIVITAS EKSTRAK SAMBILOTO (Andrographis paniculata) SEBAGAI ANTIHIPERGLIKEMIA PADA STUDI IN VIVO DIABETES MELITUS - Putri Diani Salsabillah (2022)
Hyperglycemia is a common symptom of diabetes mellitus (DM) when blood sugar levels are above normal. Traditional herbal plant are being tested to treat DM. One of the traditional herbal plant that can be used to lower glucose is Sambiloto or Andrographis paniculata. The aim of this study is to determine the effectiveness the extract of Sambiloto (Andrographis paniculata) as antihyperglycemic agents in electronic databases PubMed, DOAJ, Science Direct, and Google Scholar and created in September 2021. Results: A. paniculata extract can lower risk glucose through several pathways: antioxidant, increases Langerhans beta levels, stimulates glucose metabolism 4 (GLUT4) and increases blood glucose levels inisalini pancreas. Conclusions: A. paniculata extract is effective as an antihyperglycemic agent in rats and mice.